Genetic diversity of vector-borne zoonotic pathogens in companion dogs and cats, Tianjin, China - Jian, Rui; Xue, Jing; Xu, Ze-Yun; Chen, Si-Si; Wang, Fang-Ni; Du, Luanying; Xie, Guang-Cheng; Guo, Wen-Ping (Frontiers in Veterinary Science, 2024)
Background: Dogs and cats are the hosts of many vector-borne human pathogens that can be transmitted to humans. Given their direct and intimate contact with humans, companion dogs and cats are considered direct sentinels of vector-borne human pathogens. However, limited information is currently available regarding canine and feline zoonotic pathogens in China.This study detected canine and feline vector-borne human pathogens to better understand the potential risk to humans.Methods: Blood samples were collected from 275 domestic companion animals (117 dogs and 158 cats) living in Tianjin City, China, and the presence of DNA from Anaplasma, Babesia, Bartonella, and Rickettsia was detected by semi-nested polymerase chain reaction (PCR). The PCR products of expected size were sequenced, and these newly generated sequences were subjected to BLASTN, nucleotide identity and phylogenetic analyses.Results: Twenty-four blood samples tested positive for vector-borne pathogens in companion dogs and cats in Tianjin City, China, with a relatively low positive rate of 8.7%. Specifically, seven human pathogens, including Rickettsia raoultii, Candidatus R. jingxinensis, R. sibirica, R. felis, Babesia venatorum, Bartonella tribocorum and Bar. henselae were identified. In addition, Anaplasma ovis with zoonotic potential and Candidatus A. cinensis were detected.Our results indicate substantial genetic diversity in the vector-borne human pathogens circulating in companion dogs and cats. Interventions based on "One Health" should be taken to reduce the potential risks of contracting infection from companion dogs and cats in Tianjin, China.